Temporal changes in diabetes prevalence and achievement of care goals in urban South Asia from 2010 to 2016 – The Center for Cardio‐metabolic Risk Reduction in South Asia Study. Issue 2 (2nd November 2020) - Anjana, Ranjit Mohan; Deepa, Mohan; Subashini, Radhakrishnan; Patel, Shivani A.; Kondal, Dimple; Unnikrishnan, Ranjit; Tandon, Nikhil; Prabhakaran, Dorairaj; Narayan, K. M. Venkat; Kadir, Muhammad M.; Mohan, Viswanathan; Ali, Mohammed K.
Abstract: Aim: Achievement of treatment targets among individuals with diabetes remains suboptimal in many parts of the globe. We aimed to assess changes in diabetes prevalence and achievement of diabetes care goals in South Asia using two consecutive cross‐sectional population‐based surveys. Methods: Two representative samples of South Asian adults were recruited using identical methods from Chennai, Delhi, and Karachi in 2010‐11 (n = 16, 288; response rate–94.7%) and 2015‐16 (n = 14, 587; response rate–94.0%) through the Center for Cardio‐metabolic Risk Reduction in South Asia (CARRS) Study. Quality of care goals were defined as HbA1c <53 mmol/mol (7.0%), blood pressure (BP) control: <140/90 mmHg, lipid control: LDL cholesterol <2.56 mmol/l (100 mg/dl), and self‐reported non‐smoking. Results: Weighted prevalence of self‐reported diabetes increased by 9.0% [13% (95%CI: 13–14) to 15% (14–15)] while that of newly diagnosed diabetes decreased by 16% [6.1% (5.7–6.6) to 5.1% (4.6–5.6)]. There were improvements in achieving glycaemic (25% to 30%, p = 0.002) and lipid (34% to 45%, p < 0.001) goals, but no notable improvements in BP control or smoking status. The proportion of individuals with self‐reported diabetes meeting more than one target also increased. Conclusions: Diabetes prevalence continues to grow among urban South Asians and large gaps still exist in the attainment of treatment targets. Concerted policy, systemic, clinical and individual efforts are needed to close these care gaps.